Elaboration Participative de Scenarios de GDT a l'aide des Outils d'Analyse de Systemes a l'Echelle du Bassin Versant, Guiding questions and discussion. - Zucca, Claudio; Le, Quang Bao (2017)
This presentation presented guiding questions and discussion about the iLAMPT tool. It comes under the second session 'Evaluations of impacts of SWC planning scenarios on soil erosion across Rmel watershed' of the workshop "Systems Tool-aided Participatory Development of Sustainable Land Management Scenarios: 2nd Workshop", held in Zaghouan on 14-15 March 2017. This activity is under the output activity "User-friendly, interoperable online tool, containing country-specific, accessible knowledge base of standardized, geo-referenced SLM, to enable stakeholders to query SLM options in different context" of the GIZ funded project 'Impact evaluation of SLM options to achieve land degradation neutrality'